Moslem Mosque, Trinidad and Tobago - Sobrian, C. (Art Photo Studio, Trinidad, 2010)
Photo of mosque in St. Joseph, Trinidad and Tobago. No. 67890-B
Colour: White, Green, Brown and Blue Hues; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Mosques--Trinidad and Tobago; Buildings--Trinidad and Tobago; Islam--Trinidad and Tobago; Muslims--Trinidad and Tobago; Outbuildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Architecture, Asian--Trinidad and Tobago; Islamic architecture--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--St. Joseph